Implementasi Sistem Pembayaran Non Tunai di Kota Betun Kabupaten Malaka - Anastasia Bernaria Klau; Fransina W. Ballo; Novi Theresia Kiak (Jurnal Ekonomi Manajemen Akuntansi, 2025)
This research discusses the implementation of a non-cash payment system in Betun City, Malacca Regency. This study aims to find out how to implement the non-cash payment system, as well as to find out the supporting and inhibiting factors in the implementation of non-cash payments. This study uses a qualitative research approach with a qualitative descriptive research type. The data sources used in this study are primary data and secondary data. The data collection techniques in this study are observation, interviews and documentation. The results of this study show that the implementation of the non-cash payment system in Betun City, Malacca Regency has not been fully implemented by the people of Betun City, Malacca Regency using non-cash payments. Supporting factors in the implementation of the non-cash payment system in Betun City, Malacca Regency, are the cooperation between banks and the government and socialization to the community. The factors inhibiting the implementation of non-cash payments in the city of Betun, Malacca Regency are still low human resources and unstable internet networks.